The role of Abu Ḥanifah’s trade life in the modern economic thought - Kayadibi, Saim; Belem, Moctar (IIUM Press, 2011)
Practical life experiences of economists play a great role in creating economic theories for a prudent society. Isolated ideas from the life of an economist would not find acceptance therefore an analysis of Abū Ḥanīfah’s trade life, which gave him an intensively absorbed knowledge of how to deal with the common practices and needs of the people and newly-occurring problems of daily life. This research aims to investigate the role of Abū Ḥanīfah’s trade life and how his daily life experiences helped to materialize a manner of addressing economic issues. Many modern economic theories and banking systems have been influenced by Muslim economists and one of them was Abū Ḥanīfah. Investigating his practical experiences in trade life may contribute new understanding to modern economic thought. Global economists should possess both an ethical and practical comprehension of economics and finance rather than having solely theoretical knowledge. This has been exemplified in Malaysia, a country which is becoming a centre of Islamic Banking and Finance activities. New economists are in need of a more pragmatic and ethical comprehension of economic life in order to develop discreet view on Economic and Finance issues faced particularly by the Muslim community in the world.